Pyrite / Zn-Al LDH photo-Fenton composite catalyst as well as preparation method and application thereof
The pyrite/Zn-Al LDH photofenton composite catalyst was synthesized by high-energy ball milling method to form a heterojunction, which solved the problems of low OH utilization rate and low photofenton efficiency in traditional Fenton oxidation technology, and achieved efficient degradation of florastar Antibiotic-like and improve OH yield.
Patent Information
- Application Number
- CN202411538419.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional Fenton oxidation technology has problems in wastewater treatment with low OH utilization, limited pH conditions and iron sludge production. The photofenton method is relatively low in the treatment of difficult-to-degrade organic pollutants, and the photocatalytic performance of pyrite Less research.
The high-energy ball milling method was used to synthesize pyrite/Zn-Al LDH photofenton composite catalyst, and heterojunction was formed by dry grinding and wet grinding to improve the catalytic performance of the catalyst and improve the OH yield under visible light.
It has achieved efficient degradation of floxacin antibiotics, with good stability and reusability, broadened the visible light response range of pyrite, improved the Fe2+/Fe3+ cycle process and H2O2 decomposition, and improved the OH yield.
Smart Images

Figure CN119303598A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a pyrite / Zn-Al LDH photo-Fenton composite catalyst and a preparation method and application thereof. Background Art
[0002] At present, Fenton oxidation technology, as a kind of advanced oxidation process (AOPs), is widely used in wastewater treatment. Fenton oxidation technology is mainly to construct Fe 2+ / H2O2 system, because it can produce highly active hydroxyl (·OH) free radicals, which can oxidize a variety of organic pollutants. However, the traditional Fenton reaction has disadvantages such as low ·OH utilization, limited pH conditions (pH = 2.5 ~ 3.5) and the production of iron sludge (Fe(OH)3). Due to the low amount of iron sludge produced, the photo-Fenton method has received widespread attention for the treatment of refractory organic pollutants. The introduction of light can react with Fe 2+ The synergistic catalysis can produce more ·OH, thereby improving the oxidation efficiency of the photo-Fenton oxidation process.
[0003] Natural mineral materials are widely present in nature, and most of them have been shown to have excellent catalytic properties and can be used to degrade pollutants in Fenton systems. Among them, pyrite is the most abundant metal sulfide mineral in nature and has excellent catalytic properties. However, there are few studies on the photocatalytic properties of pyrite. In fact, due to the narrow band gap (0.95 eV) and the resulting strong sunlight absorption ability, pyrite exhibits excellent photocatalytic properties under light irradiation, which is conducive to its application in photo-Fenton systems and photocatalytic reactions. Therefore, it is of great significance to prepare a composite photo-Fenton material based on pyrite to achieve the purpose of making full use of natural resources and improving photocatalytic performance.
[0004] Layered double hydroxides (LDHs) are two-dimensional (2D) anionic clay materials with octahedral symmetry. Because of their similar structure to hydrotalcite, they are commonly known as hydrotalcite. Various methods for synthesizing layered double hydroxides have been widely reported, including coprecipitation, urea method, hydrothermal method, anion exchange method, etc., but they all have various disadvantages. Therefore, it is still necessary to find a simple, environmentally friendly, and large-scale LDHs synthesis method. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a pyrite / Zn-Al LDH photo-Fenton composite catalyst and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a pyrite / Zn-Al LDH photo-Fenton composite catalyst comprises the following steps:
[0009] Mix pyrite, zinc source and aluminum source, add zirconium oxide grinding balls, and perform dry grinding;
[0010] Adding water to the material obtained by dry grinding to perform wet grinding;
[0011] A sodium carbonate solution is added to the material obtained by wet grinding to react, and the material after the reaction is washed and dried to obtain the pyrite / Zn-Al LDH photo-Fenton composite catalyst, which is recorded as Pyrite / Zn-Al LDH photo-Fenton composite catalyst.
[0012] In the preparation method of the pyrite / Zn-Al LDH photo-Fenton composite catalyst of the present invention, the dry grinding process mainly subdivides the bulk material, mixes the pyrite, zinc source and aluminum source, and makes the surface contact more sufficient, thereby providing sufficient physical contact for the next wet grinding; the wet grinding process mainly adds ultrapure water to supplement the crystallization water necessary for the formation of Zn-Al LDH, so that the zinc source and the aluminum source fully form Zn-Al LDH, and forms a heterojunction with the pyrite on the contact surface by solid phase grinding, thereby effectively improving the performance of the composite catalyst.
[0013] Preferably, the mass ratio of the pyrite, zinc source and aluminum source is (0.8-1): (2-4): 1, more preferably 1: 3: 1. When the zinc source is too low (2: 1), the zinc-aluminum hydrotalcite will form a (001) crystal plane, and as the mass ratio of the zinc source increases to 3: 1, the catalyst hydrotalcite can successfully form an effective crystal plane (003), and the crystal plane has a high crystallinity, and as the mass ratio further increases (4: 1), the effective crystal plane (003) crystallinity in Zn-Al LDH will decrease. Therefore, the mass ratio of the pyrite, zinc source and aluminum source is preferably 1: 3: 1.
[0014] Preferably, the zinc source is zinc nitrate hexahydrate (Zn(NO3)2·6H2O), and the aluminum source is aluminum oxide (Al2O3).
[0015] Preferably, the material ratio of the zirconia grinding balls is 10 to 50. The term "material ratio of the zirconia grinding balls" refers to the mass ratio of the zirconia grinding balls to the material to be ground.
[0016] More preferably, the material ratio of the zirconia grinding balls is 30.
[0017] Preferably, during dry grinding and wet grinding, the ball milling speed is 100-500 rpm and the time is 1-8 h.
[0018] More preferably, during dry milling and wet milling, the ball milling speed is 250 rpm and the time is 6 h.
[0019] Preferably, the concentration of the sodium carbonate solution is 0.01-0.5 mol / L, more preferably 0.1 mol / L.
[0020] Preferably, after adding the sodium carbonate solution, the reaction temperature is 50-100° C. and the reaction time is 1-5 h.
[0021] Preferably, the washing is: repeatedly washing the reacted material with deionized water until the supernatant is neutral.
[0022] Preferably, the drying is vacuum drying, the drying temperature is 20-100° C., preferably 85° C., and the drying time is 8-12 h.
[0023] Preferably, the screening is to use a sieve to screen the dried material, and the aperture of the sieve is 50-200 mesh.
[0024] The present invention uses a high-energy ball milling method for the first time to prepare a pyrite-based composite hydrotalcite photo-Fenton catalyst (i.e., pyrite / Zn-Al LDH photo-Fenton composite catalyst), forming a heterojunction at the solid-phase surface interface, thereby greatly improving the catalytic ability of pyrite.
[0025] The second technical solution of the present invention:
[0026] The present invention also provides a pyrite / Zn-Al LDH photo-Fenton composite catalyst prepared according to the method.
[0027] The third technical solution of the present invention:
[0028] The invention also provides application of the pyrite / Zn-Al LDH photo-Fenton composite catalyst in treating floxacin antibiotics.
[0029] Preferably, the floxacin antibiotic is ciprofloxacin (CIP), ofloxacin (OFX) and / or norfloxacin (NOR).
[0030] Pyrite / Zn-Al LDH (P / ZA-LDH) photo-Fenton composite catalyst prepared by high-energy ball milling in the present invention not only has a good treatment effect on pyrite antibiotics, but also has good stability and reusability. The present invention uses mechanical ball milling to form a heterojunction at the solid-phase surface interface, thereby greatly improving the catalytic ability of pyrite. The reaction mechanism is as follows: Under visible light irradiation, Zn-Al LDH cannot be excited, while the active components of pyrite in P / ZA-LDH can be excited by visible light, thereby generating photogenerated electron holes (e - -h+ ) Yes. Since the CB position of Pyrite in Zn-Al LDH is relatively negative, the e on the CB of Pyrite - It can directly migrate to the CB of Zn-Al LDH. The electron transfer from Pyrite to Zn-Al LDH increases the charge separation, thus enhancing the photocatalytic performance of P / ZA-LDH. Zn-Al LDH acts as a reaction platform to promote the formation of dissolved O2·O2 - , and then converted to ·OH. At the same time, the VB of Zn-Al LDH is higher than the standard redox potential ·OH / OH - This proves that the holes on the VB of Zn-Al LDH can transfer OH - Oxidized to ·OH, and ·OH can also be oxidized to ·OH through H2O2 and ·O2 - or e - Reaction generation. When Pyrite exists in P / ZA-LDH, Fe(III) on the surface of Pyrite can be reduced to Fe(II) through the Haber-Weiss cycle. The reduced Fe(II) can react with H2O2 to form a photo-Fenton system, generating ·OH radicals to effectively degrade oxazolidinone pollutants.
[0031] Compared with the prior art, the present invention has the following advantages and technical effects:
[0032] The present invention proposes for the first time to use a two-step high-energy ball milling method to synthesize a Pyrite / Zn Al-LDH photo-Fenton composite catalyst, which can prepare a catalyst with good performance without high-temperature calcination. Among them, the ball milling preparation method is green and environmentally friendly, more energy-efficient, and easy to use on a large scale in industrial scenarios. In addition, the natural mineral pyrite is used as a raw material to load Zn-Al LDH to form a heterojunction, which broadens the visible light response range of a single pyrite. Compared with the traditional Fenton system, the constructed photo-Fenton system has a higher visible light response range than the traditional Fenton system under visible light irradiation. 2+ / Fe 3+ The cycle process and the decomposition of H2O2 are improved, thereby increasing the yield of ·OH, and having a certain universality for floxacin antibiotics (ciprofloxacin, ofloxacin, norfloxacin). In the preparation method of the present invention, the reaction process is simple and easy to control, the cost is low, and the product Pyrite / Zn Al-LDH photo-Fenton composite catalyst has high catalytic activity and high stability under visible light. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0034] Figure 1(a) is an X-ray powder diffraction (XRD) pattern of the catalysts prepared in Examples 1 to 3, and (b) is a Fourier transform infrared spectrum (FTIR) pattern of pure pyrite (Pyrite), Zn Al-LDH and the catalyst prepared in Example 1 (P / Z A-LDH-2);
[0035] Figure 2 The scanning electron microscope (SEM) and high-resolution transmission electron microscope (HRTEM) images of the catalysts prepared in Example 1, wherein (a) Pyrite, (b) Zn Al-LDH, (c)-(f) P / Z A-LDH-2;
[0036] Figure 3 The optical performance diagrams of pure pyrite (Pyrite), Zn Al-LDH and the catalyst prepared in Example 1 (P / Z A-LDH-2), wherein (a) is the UV-visible diffuse reflectance spectrum, and (b) is the band gap energy level;
[0037] Figure 4 The results of the photo-Fenton degradation of ciprofloxacin (CIP) by the catalysts prepared in Examples 1 to 3 are shown in Figure 1, where (a) is the degradation curve of CIP by P / Z A-LDH at different Zn / Al ratios, and (b) is the apparent rate constant k app curve;
[0038] Figure 5 CIP degradation curve (a) and first-order kinetic constant k of the catalyst prepared in Example 1 under different reaction systems app Figure (b), where P / Z A-LDH-2 / H2O2 / Vis represents the k of the catalyst in Example 1 under the photo-Fenton system. app Value, P / ZA-LDH-2 / H2O2 / Dark represents the degradation k of Example 1 under the Fenton system app The value, P / Z A-LDH-2 / Vis, represents the k value of the catalyst in Example 1 under the photocatalytic system. app Value, Zn Al-LDH / H2O2 / Vis represents the k value of the catalyst in Example 1 under the Fenton system app Py / H2O2 / Dark represents the k value of pyrite catalyst in Fenton system. app Py / Vis represents the k value of pyrite catalyst in the photocatalytic system. app The value of H2O2 / Vis represents the k value of pyrite catalyst in the photo-Fenton system. app value;
[0039] Figure 6The photo-Fenton catalytic degradation results of three floxacin antibiotics (ciprofloxacin (CIP), ofloxacin (OFX) and norfloxacin (NOR)) by the catalyst prepared in Example 1: (a) is the degradation curve of P / Z A-LDH-2 for CIP, OFX and NOR, and (b) is the corresponding first-order kinetic curve;
[0040] Figure 7 Figure 1 is a diagram of actual application scenarios: (a) the recycling performance of the catalyst prepared in Example 1, (b) the ion leaching amount of the catalyst prepared in Example 1 after the cyclic catalytic reaction, (c) a physical picture of natural lake water, and (d) the photo-Fenton degradation results of CIP by the catalyst prepared in Example 1 in ultrapure water (Ulptrapure water), tap water (Tap water) and lake water (Lake water) systems. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] All raw materials used in the examples of the present invention are purchased from commercial sources. As an example, the pyrite in the examples is from Tongling Runlong Industrial Co., Ltd.
[0047] The technical solution of the present invention is further illustrated by the following embodiments.
[0048] Example 1
[0049] (1) 0.5 g of pyrite, 1.5 g of Zn(NO3)2·6H2O and 0.5 g of Al2O3 were weighed and added into a zirconia ball mill, the material ratio of zirconia grinding balls was 30, and the mixture was ball milled at 250 rpm for 6 h to obtain a mixture A;
[0050] (2) adding 1.5 mL of deionized water to the mixture A, and continuing to ball mill the aqueous mixture for 2 h at the same ball milling speed to obtain a mixture B;
[0051] (3) Mixture B was immersed in 0.1 mol / L Na2CO3 and reacted at 80°C for 2 h to obtain mixture C;
[0052] (4) The mixed material C was repeatedly rinsed with deionized water until the pH of the supernatant was 7; the obtained solid sample was vacuum dried in an oven at 85°C overnight, and the obtained solid was fully ground to obtain powder D, which was passed through a 200-mesh sieve to obtain a pyrite / Zn-AlLDH photo-Fenton composite catalyst, denoted as Pyrite / Zn Al-LDH-2, abbreviated as P / Z A-LDH-2.
[0053] Example 2
[0054] The difference between this example and example 1 is that the amount of Al2O3 in step (1) is changed to 0.75 g, and the obtained composite catalyst is recorded as P / Z A-LDH-1.
[0055] Example 3
[0056] The difference between this example and example 1 is that the amount of Al2O3 in step (1) is changed to 0.375 g, and the obtained composite catalyst is recorded as P / Z A-LDH-3.
[0057] Example 4
[0058] The difference between this embodiment and embodiment 1 is that the amount of pyrite in step (1) is changed to 0.4 g.
[0059] Example 5
[0060] (1) 0.5 g of pyrite, 1.5 g of Zn(NO3)2·6H2O and 0.5 g of Al2O3 were weighed and added into a zirconia ball mill, the material ratio of zirconia grinding balls was 10, and the mixture was ball milled at 100 rpm for 8 h to obtain a mixture A;
[0061] (2) adding 1.5 mL of deionized water to the mixture A, and continuing to ball mill the aqueous mixture for 6 h at the same ball milling speed to obtain a mixture B;
[0062] (3) Mixture B was immersed in 0.5 mol / L Na2CO3 and reacted at 50°C for 5 h to obtain mixture C;
[0063] (4) The mixed material C was repeatedly rinsed with deionized water until the pH of the supernatant was 7; the obtained solid sample was vacuum dried in an oven at 20°C for 12 hours, and the obtained solid was fully ground to obtain powder D, which was then sieved through a 100-mesh sieve to obtain a pyrite / Zn-AlLDH photo-Fenton composite catalyst.
[0064] Example 6
[0065] (1) 0.5 g of pyrite, 1.5 g of Zn(NO3)2·6H2O and 0.5 g of Al2O3 were weighed and added into a zirconia ball mill, the material ratio of zirconia grinding balls was 50, and the mixture was ball milled at 500 rpm for 1 h to obtain a mixture A;
[0066] (2) adding 1.5 mL of deionized water to the mixture A, and continuing to ball mill the aqueous mixture for 6 h at the same ball milling speed to obtain a mixture B;
[0067] (3) Mixture B was immersed in 0.01 mol / L Na2CO3 and reacted at 100°C for 1 h to obtain mixture C;
[0068] (4) The mixed material C was repeatedly rinsed with deionized water until the pH of the supernatant was 7; the obtained solid sample was vacuum dried in an oven at 100° C. for 8 h, and the obtained solid was fully ground to obtain powder D, which was then sieved through a 50-mesh sieve to obtain a pyrite / Zn-AlLDH photo-Fenton composite catalyst.
[0069] Comparative Example 1 Preparation of Zn Al-LDH
[0070] The difference between this embodiment and embodiment 1 is that the step of adding pyrite in step (1) of embodiment 1 can be omitted.
[0071] Comparative Example 2
[0072] The difference between this embodiment and embodiment 1 is that the added amount of Zn(NO3)2·6H2O is 2.5 g.
[0073] Figure 1 (a) is the X-ray powder diffraction (XRD) diagram of the catalysts prepared in Examples 1 to 3, and (b) is the Fourier transform infrared spectrum (FTIR) diagram of pure pyrite (Pyrite), Zn Al-LDH and the catalyst prepared in Example 1. From the XRD diagram, it can be clearly observed that the hydrotalcite-like LDH material and the typical characteristic peaks corresponding to Fe2S derived from Pyrite. The obtained product matches the simulated standard cards Fe2S (JCPDS No.71-0053) and Zn-Al LDH (JCPDS No.38-0486 and No.48-1849), indicating that the composite materials P / Z A-LDH are successfully prepared. Fourier transform infrared spectrometer (FTIR) further analyzes and studies the structure and interaction of the catalyst. 3750cm -1 -3400cm -1 The peak at 1638cm belongs to the stretching vibration mode of adsorbed water and the hydroxyl group (-OH) on the surface of adsorbed water. -1 The weak and broad peak at 1383 cm corresponds to the bending vibration of interlayer water molecules. -1 The peak at is attributed to interlayer CO3 2- Bending vibration of the bond. 1088cm -1 S = S SO4 2- The peak at 614 cm was improved in P / Z A-LDH-2 due to the formation of sulfate during the oxidation of pyrite. -1 With 422cm -1 The peaks at are attributed to MO or OMO (M = Fe, Zn, Al). In the infrared signal of the composite material P / Z A-LDH-2, the main characteristic peaks of Pyrite and Zn Al-LDH can be clearly observed, further proving the successful composite of the two.
[0074] Figure 2 The scanning electron microscope (SEM) and high-resolution transmission electron microscope (HRTEM) images of the catalyst prepared in Example 1 show that the surface morphology of pyrite is a smooth block structure, and the Zn-Al hydrotalcite exhibits an irregular flaky structure. The P / Z A-LDH-2 composite material prepared by the high-energy ball milling method is composed of a block and a flaky composite, and the surface of the block pyrite is loaded with a large amount of irregular flaky Zn-Al hydrotalcite. Figure 2 The TEM image in (d) further confirms the morphology of the composite material. The lattice fringes of pyrite and ZnAl hydrotalcite are clearly visible, forming a heterojunction nanostructure. Figure 2From the HRTEM image in (f), it can be seen that the interplanar spacing is 0.271nm, 0.243nm and 0.259nm, corresponding to the (2 0 0) crystal plane of pyrite, the (21 0) crystal plane of Zn-Al hydrotalcite and the (0 1 2) crystal plane of Zn-Al hydrotalcite, respectively. This further indicates that the prepared P / Z A-LDH-2 composite catalyst was successfully synthesized.
[0075] UV-visible diffuse reflectance spectroscopy ( Figure 3 ) studied the photoresponse characteristics of Pyrite, Zn Al-LDH and P / Z A-LDH-2. The catalysts all showed high visible light absorption capacity. Among them, P / Z A-LDH-2 showed the highest peak intensity. This is because the efficient composite of Pyrite and Zn Al-LDH formed a heterojunction, which reduced the optical band gap. Additional intermediate energy states were generated between the valence band and conduction band of P / Z A-LDH-2, which extended the light absorption of the sample to longer wavelengths and enhanced the absorption intensity, resulting in more photogenerated carriers on the catalyst surface. The band gap energy (Eg) of the catalyst was calculated by the Tauc plot method and the Kubelka-Munk equation, and the band gap value of the prepared semiconductor catalyst was obtained. Among them, the band gaps of Pyrite, Zn Al-LDH and P / ZA-LDH-2 were 1.81eV, 3.37eV and 1.40eV, respectively. Compared with pure Pyrite, the band gap value of the composite material P / Z A-LDH-2 is reduced, which indicates that after Pyrite is combined with Zn Al-LDH, it can more effectively promote the separation of photogenerated electrons and holes, and a large number of photoexcited carriers react with sulfoxide pollutants, thereby enhancing the photo-Fenton catalytic performance of the material.
[0076] Experimental verification
[0077] The photo-Fenton catalytic performance of the P / Z A-LDH catalyst prepared above (hereinafter referred to as "sample") was tested under different conditions. The specific method is as follows: 12.5 mg of sample was dispersed in 25 mL of organic pollutant solution. Stir for 30 minutes in the dark before illumination to ensure that the sample and the pollutant reached adsorption and desorption equilibrium, and then 5 mM H2O2 was added to the test tube. Circulating water was used in the reaction device to maintain the temperature at 25 ± 2 ° C. 1 mL of the suspension was taken out every 10 minutes and filtered through a needle filter of polyethersulfone (PES) with a pore size of 0.45 μm. The concentration of floxacin antibiotics in the filtrate was measured and the degree of degradation after the catalyst was removed was compared. Cyclic test On this basis, the sample was retained after each test, washed and dried, and the test was repeated five times to obtain a complete cycle test result.
[0078] The results of photo-Fenton degradation of ciprofloxacin (CIP) by the catalysts prepared in Examples 1 to 3 are shown in FIG. Figure 4After 60 minutes of reaction, the removal rate of ciprofloxacin was over 80%, among which the catalyst of Example 1 showed the best catalytic degradation ability.
[0079] CIP degradation curves (a) and first-order kinetic constants k of the catalyst prepared in Example 1 under different reaction systems app See Figure (b) for the value Figure 5 , after 60 minutes of reaction, the concentration of CIP did not change significantly. Therefore, it can be considered that during the experiment, CIP itself will not degrade. Compared with the traditional Fenton system and photocatalytic system, the catalyst prepared by the present invention shows better degradation effect under the photo-Fenton system, because the introduction of light makes the electrons in the catalyst more easily excited. These excited electron-hole pairs can participate in the electron transfer process, thereby extending the life of free radicals. At the same time, the heterojunction present in the composite catalyst effectively improves the separation efficiency of photogenerated carriers. The results show that Example 1 has the best CIP degradation performance under the photo-Fenton system (P / Z A-LDH-2 / H2O2 / Vis).
[0080] Figure 6 This is a graph showing the photo-Fenton catalytic degradation of three floxacin antibiotics (ciprofloxacin (CIP), ofloxacin (OFX) and norfloxacin (NOR)) by the catalyst prepared in Example 1. The results show that after 60 minutes of reaction, all three floxacin antibiotics were removed in large quantities, among which the catalyst prepared in Example 1 showed the best catalytic degradation ability for CIP.
[0081] Figure 7 The figure is a diagram of a practical application scenario: (a) the recycling performance of the catalyst prepared in Example 1, (b) the ion leaching amount of the catalyst prepared in Example 1 after the cyclic catalytic reaction, (c) the physical picture of natural lake water, (d) the photo-Fenton degradation results of the catalyst prepared in Example 1 in ultrapure water, tap water and lake water systems. It can be seen that the catalyst prepared in Example 1 catalytically degrades CIP in the photo-Fenton system, and the CIP removal rate can still reach more than 85% after 5 cycles, indicating its good stability and reusability. Among them, the catalyst in Example 1 shows the best catalytic degradation ability, and the ion leaching rate results show that the ion leaching rate after five cycles is far lower than the national emission standard (Fe: 1 mg / L, GB 25467-2010; Al: 3 mg / L, GB 21900-2008; Zn: 5 mg / L, GB 8978-1996). The catalyst prepared in Example 1 in the natural lake water system still achieved a CIP removal rate of more than 70% in the photo-Fenton system, and the results showed that it has good practical application potential.
[0082] Figure 3 This shows that the band gap value of Zn-Al LDH changes after being combined with pyrite, which also proves that the material is successfully combined. At the same time, the HRTEM transmission electron microscope can also show that a heterojunction is formed at the surface interface. The catalytic effect of pyrite itself is reflected in Figure 5 In the Fenton system (without light), due to its narrow band gap width, the electron-hole recombination rate is high after visible light excitation, so the wide-gap Zn-Al LDH is introduced to optimize its band gap structure, reduce the electron-hole recombination rate, and thus improve the catalytic ability of the composite P / Z A-LDH-2; the heterojunction is formed at the solid-phase surface interface by mechanical ball milling; we don’t know what specific elements form the heterojunction, but as a heterojunction structure formed at the surface interface of two semiconductors, it can greatly enhance the catalytic ability of pyrite. The reaction mechanism is as follows: under visible light irradiation, Zn-Al LDH cannot be excited. The active component of Pyrite in P / ZA-LDH can be excited by visible light, thus generating photogenerated electron holes (e - -h + ) Yes. Since the CB position of Pyrite in Zn-Al LDH is relatively negative, the e on the CB of Pyrite - It can directly migrate to the CB of Zn-Al LDH. The electron transfer from Pyrite to Zn-Al LDH increases the charge separation, thus enhancing the photocatalytic performance of P / ZA-LDH. Zn-Al LDH acts as a reaction platform to promote the formation of dissolved O2·O2 - , and then converted to ·OH. At the same time, the VB of Zn-Al LDH is higher than the standard redox potential ·OH / OH - This proves that the holes on the VB of Zn-Al LDH can transfer OH - Oxidized to ·OH, and ·OH can also be oxidized to ·OH through H2O2 and ·O2 - or e - When pyrite exists in P / ZA-LDH, Fe(III) on the surface of pyrite can be reduced to Fe(II) through the Haber-Weiss cycle. The reduced Fe(II) can react with H2O2 to form a photo-Fenton system, generating ·OH radicals to degrade oxazolidinone pollutants.
[0083] In summary, the present invention provides a pyrite / Zn-Al LDH photo-Fenton composite catalyst and a preparation method and application thereof. The catalyst of the present invention contains pyrite and composite hydrotalcite. The raw materials used in the catalyst of the present invention are low in cost, easy to obtain, have low equipment requirements, are simple to prepare, are environmentally friendly, meet the requirements of green chemistry, and are a photo-Fenton composite catalyst that can be produced on a large scale. The catalyst of the present invention is constructed by heterogeneous structure, which not only greatly improves the degradation efficiency of the catalyst, but also effectively solves the problems of metal agglomeration and ion leaching. The catalyst of the invention can form an efficient photo-Fenton catalytic system in a natural water system, realize the rapid degradation of floxacin antibiotics (ciprofloxacin (CIP), ofloxacin (OFX), norfloxacin (NOR)), can be sustainably recycled, and the leaching of iron ions, aluminum ions and zinc ions is far lower than the limit of the national natural environment emission standard (Fe: 1 mg / L, GB 25467-2010; Al: 3 mg / L, GB 21900-2008; Zn: 5 mg / L, GB 8978-1996), and can be widely used in the fields of environmental protection, chemical industry, textile, etc.
[0084] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a pyrite / Zn-Al LDH photo-Fenton composite catalyst, characterized in that: The following steps are involved: Mix pyrite, zinc source and aluminum source, add zirconium oxide grinding balls, and perform dry grinding; Adding water to the material obtained by dry grinding to perform wet grinding; A sodium carbonate solution is added to the material obtained by wet grinding to react, and the material after the reaction is washed and dried, and the pyrite / Zn-Al LDH photo-Fenton composite catalyst is obtained after screening.
2. The method for preparing the pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 1, characterized in that: The mass ratio of the pyrite, the zinc source and the aluminum source is (0.8-1):(2-4):
1.
3. The preparation method of pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 1, characterized in that: The material ratio of zirconia grinding balls is 10-50.
4. The method for preparing the pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 3, characterized in that: The material ratio of zirconia grinding balls is 30.
5. The preparation method of pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 1, characterized in that: During dry grinding and wet grinding, the ball mill speed is 100-500rpm and the time is 1-8h.
6. The method for preparing the pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 5, characterized in that: During dry grinding and wet grinding, the ball mill speed was 250 rpm and the time was 6 h.
7. The method for preparing the pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 1, characterized in that: The concentration of the sodium carbonate solution is 0.01-0.5 mol / L.
8. The method for preparing the pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 1, characterized in that: After adding the sodium carbonate solution, the reaction temperature is 50-100° C. and the reaction time is 1-5 h.
9. A pyrite / Zn-Al LDH photo-Fenton composite catalyst, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the pyrite / Zn-Al LDH photo-Fenton composite catalyst according to claim 9 in the treatment of floxacin antibiotics.